Pengaruh Fee Audit, Audit Tenure, Dan Ukuran Perusahaan Terhadap Kualitas Audit Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024 - Agustina R.T. Sitompul; Riska Franita; An Suci Azzahra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This research endeavors to examine the influence of audit fees, audit duration, and organizational size on audit quality, considering both their individual and combined effects. The study's sample comprises multiple companies operating in the food and beverage industry that are listed on the Indonesian Stock Exchange (IDX) over the period from 2020 to 2024. This research uses associative quantitative analysis, based on supporting data from financial reports of companies published through the official IDX web portal during the same period. The population consists of 83 business entities in the food and beverage sector officially listed on the IDX. Purposive sampling was applied in selecting the study sample; from the population, 27 business entities that met the research indicators were obtained, and with this sample selection, the study analyzed 135 data points. With the use of SPSS version 26 software, data analysis was done using logistic regression techniques. The study results reveal that audit fees independently have a significant impact on audit quality standards, with a significance probability of 0.000 (< 0.05). However, audit tenure and company scale do not show significant effects on audit quality, with significance levels of 0.292 and 0.153, respectively, both exceeding 0.05. Simultaneous testing reveals that the three independent variables collectively contribute significantly to audit quality, with a significance below 0.05 (0.000).